Securitization Of Ultra Micro Financing Asset In The Form Collective Investment Credit Of Asset-Backed Securities: Conceptual Design And Tax Implication In Indonesia - Nurcahya, Wirawan Firman; Soeryanto, Djoko Koes Hery (WIM Solusi Prima, 2024)
The Government's concern for a micro-based economy has materialized through the provision of Ultra Micro (UMi) Financing to Micro, Small, and Medium Enterprises (MSMEs) by the Government Investment Center Public Service Agency or Badan Layanan Umum Pusat Investasi Pemerintah (BLU PIP). UMi financing, as part of program credit, aims to promote self-reliance among micro-businesses that are not facilitated by the banking sector. However, limited capital from the APBN can hinder the desirability of this credit program. In order to leverage UMi financing hence it can be benefitted by more MSMEs beyond the capabilities of the APBN, the Government should diversify the funding sources for micro-businesses, not solely relying on the State Budget (APBN) but also incorporating funds from other sources. To realize this objective, the Government, through BLU PIP, can securit of receivables of Ultra Micro Financing in the form of Collective Investment Credit for Asset-Backed Securities (CIC-ABS). The objective of this research is to propose a conceptual design of CIC-ABS of UMi and examine tax implication of CIC-ABS of UMi in Indonesia. The question in this research is how to create a conceptual CIC-ABS UMi that is suitable for implementation and what are the tax implications in Indonesia. The contribution of this research is that it is pioneering concept of asset leveraging of MSME credits through Collective Investment Credit for Asset-Backed Securities (CIC-ABS) and tax implication in the unique context of Indonesia. The methodology used in this research includes the conceptual design of securitization and qualitative description to analyze tax implication of securitization of UMi's financing in the form of CIC-ABS in Indonesia. The conclusion that can be drawn from this research is that the UMi CIC-ABS conceptual design is suitable for implementation in Indonesia and tax implications are CIC-ABS of UMi subject to Corporate Income Tax at 25%, Originator incurs Corporate Income Tax on profits from the transfer, ABS Holders face varying tax treatments based on ABS class, and CIC-ABS of UMi is exempt from Value Added Tax (VAT).